Autonomous agents : from self-control to autonomy - Mele, Alfred R., 1951- (New York : Oxford University Press, 1995)
Alfred Mele examines the concept of self-control on its terms, followed by an examination of its bearing on one's actions, beliefs, and emotions. He considers how, by understanding self-control, man can shed light on autonomous behaviour.
Intro -- Contents -- PART I -- 1. Introduction: Self-Control and Personal Autonomy -- 2. Better Judgment: Nature and Function -- 3. Exercising Self-Control: A Motivational Problem -- 4. Self-Control, Akrasia, and Second-Order Desires -- 5. Self-Control and Belief -- 6. Self-Control, Akrasia, and Emotion -- 7. The Upper Reaches of Self-Control and the Ideally Self-Controlled Person -- PART II -- 8. Transition: From Self-Control to Autonomy -- 9. Psychological Autonomy and Personal History -- 10. Compatibilist Autonomy and Autonomous Action -- 11. Problems for Libertarians -- 12. Incompatibilist Autonomy and Autonomous Action -- 13. Assessing the Denial of Autonomy -- References -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z.
Includes bibliographical references (pages 257-264) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Self-control.; Autonomy (Philosophy); Maîtrise de soi; Autonomie (Philosophie); PHILOSOPHY -- Movements -- Humanism; Autonomy (Philosophy); Self-control